Objective Sensory Testing Methods Reveal a Higher Prevalence of Olfactory Loss in COVID-19–Positive Patients Compared to Subjective Methods: A Systematic Review and Meta-Analysis. (29th September 2020) - Hannum, Mackenzie E; Ramirez, Vicente A; Lipson, Sarah J; Herriman, Riley D; Toskala, Aurora K; Lin, Cailu; Joseph, Paule V; Reed, Danielle R
Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes coronavirus disease 2019 (COVID-19), has currently infected over 6.5 million people worldwide. In response to the pandemic, numerous studies have tried to identify the causes and symptoms of the disease. Emerging evidence supports recently acquired anosmia (complete loss of smell) and hyposmia (partial loss of smell) as symptoms of COVID-19, but studies of olfactory dysfunction show a wide range of prevalence from 5% to 98%. We undertook a search of Pubmed/Medline and Google Scholar with the keywords "COVID-19, " "smell, " and/or "olfaction." We included any study that quantified smell loss (anosmia and hyposmia) as a symptom of COVID-19. Studies were grouped and compared based on the type of method used to measure smell loss—subjective measures, such as self-reported smell loss, versus objective measures using rated stimuli—to determine if prevalence differed by method type. For each study, 95% confidence intervals (CIs) were calculated from point estimates of olfactory disturbances. We identified 34 articles quantifying anosmia as a symptom of COVID-19 (6 objective and 28 subjective), collected from cases identified from January 16 to April 30, 2020. The pooled prevalence estimate of smell loss was 77% when assessed through objective measurements (95% CI of 61.4–89.2%) and 44% with subjective measurements (95% CI of 32.2–57.0%). Objective measures are a more sensitive method to identify smell loss as a result of infection with SARS-CoV-2; the use of subjective measures, while expedient during the early stages of the pandemic, underestimates the true prevalence of smell loss.